Bridging tradition and modernity in Thai Islam: the political and religious roles of Surin Pitsuwan (Abdul Halim) - Yusuf, Imtiyaz; Pham, Thuy Quynh (IIUM Press, 2023)
Dr Surin Pitsuwan (Abdul Halim bin Ismail Pitsuwan) (28 October 1949 – 30 November 2017) was a prominent Thai Muslim politician of national and international stature with a colorful career as a journalist, an academic, a member of the Parliament and served first as Deputy Foreign Minister and ​next as the​ Foreign Minister of Thailand from 1992 to 2001, culminating in his career as the Secretary General of the Association of Southeast Asian Nations (ASEAN) between 2008 and 2013. Born and bred in a traditional Malay family in Nakhon Si Thammarat, he acquired the pondok and modern education in Thai and American universities. He played an important role in bridging tradition and modernity in Thai Islam by promoting the Thai Muslim community's educational, intellectual, and political upliftment, thereby constructing its integrative face of Islam in Thailand - a Buddhist-majority country. Dr Pitsuwan was an ardent promoter of democratic practice, human resources development and upholding human rights through peaceful means. This article employs qualitative and subjective approaches by drawing data from the speeches, writings, and personal interactions with Dr Pitsuwan. It highlights that peaceful coexistence between the ​Thai ​Muslims and ​the Thai Buddhists​ ​is a reality ​and not an exception